2016
DOI: 10.3390/ijerph13080800
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cough Prevalence with Ambient Polycyclic Aromatic Hydrocarbons, Nitrogen and Sulphur Dioxide: A Longitudinal Study

Abstract: Information on potential cough triggers including environmental irritants is vital for successful management of chronic cough in patients. We investigated the relationship between ambient levels of particulate polycyclic aromatic hydrocarbons (PAH), nitrogen dioxide (NO2) and sulphur dioxide (SO2) exposures with cough prevalence. Eighty-three adult patients, who had been physician diagnosed with at least asthma, cough variant asthma and/or atopic cough, were divided into asthma and non-asthma groups. They reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(67 reference statements)
2
6
0
Order By: Relevance
“…It has been considered that these organic and inorganic pollutants were simultaneously long-range transported to Japan by westerly winds. They are thought to be common causes of hospital admission for respiratory, cerebrovascular, and cardiovascular diseases [10], cough prevalence [11][12][13], itchy eyes [14], asthma exacerbation [15], and seasonal allergic rhinitis [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered that these organic and inorganic pollutants were simultaneously long-range transported to Japan by westerly winds. They are thought to be common causes of hospital admission for respiratory, cerebrovascular, and cardiovascular diseases [10], cough prevalence [11][12][13], itchy eyes [14], asthma exacerbation [15], and seasonal allergic rhinitis [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…The Pearson correlation analysis was used to examine the correlation between daily concentrations of air pollutants, including PAH and TSP. The generalized estimating equations (GEEs) were used to examine the relationship between cough occurrence and PAH exposure [6]. GEE models for same-day (lag 0 defined as 24 h period before the health response) through 5 day lag were constructed with adjustments for potential confounders; monitoring sites, gender, age, body mass ranking, and the presence or absence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Among these routes, inhalation has been considered more important for the respiratory effects of PAHs [3]. PAHs are now shown to be involved in the development and exacerbation of respiratory diseases, such as childhood and adult BA, chronic obstructive pulmonary disease, and others accompanied by cough symptoms, in addition to affecting respiratory function [3,4,6,7]. However, a few epidemiological studies have demonstrated the possible association between airborne PAH exposure and respiratory symptoms, such as cough prevalence in people with chronic respiratory diseases, including asthma [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent Japanese study found that exposure to polycyclic aromatic hydrocarbon, nitrogen dioxide and sulfur dioxide was associated with an increase in cough prevalence among adults with chronic cough. 29 In a cross sectional survey of 200 Russian adults, exposure to heavy mining and refining industrial air pollution was also associated with chronic cough, after adjustment for smoking status, age and sex (OR 2.16, 95% CI 1.07–4.35). 30 Living close (<100 m) to a major road in Beijing, China led to a higher risk of chronic cough compared to living >200 m (OR 2.54, 95% CI 1.57–4.10).…”
Section: Research Into An Obvious Etiology or Aggravating Factormentioning
confidence: 99%